Employment Relations and the Performance of Government Entities: A Case Study of Kabale District Local Government. - Asiimwe, Jackline (Kabale University, 2023)
The study considered the relationship between employee relations and organizational performance in Kabale District Local Government. The study was guided by the impact of employee relations on the performance of the government entities with a specific case study of Kabale District Local Government, the relationship between employee relations and organizational performance of government entities with the specific case study of Kabale District Local Government and the challenges faced by the employees in the government organizations. The study used a descriptive research design that aimed at generating information after the incident had occurred; the Qualitative approach included the use of interviews. Data was collected using a questionnaire and interview guide, simple random and purposive sampling methods were used. Both qualitative and quantitative methodologies were used to analyze data as a sample size of 50 respondents was used. The study revealed that the impact of employee relations used at Kabale district local government include; regulations and agreements by which employees are managed both as individuals and the organization, promotes teamwork which achieves organization goals, and employees will be treated fairly and honestly. The study revealed that some of the relationship between employee relation and organizational performance of government entities were employee relationship is the major factor determining the performance of employees, beliefs, and behavior of the enterprises employees are held to occupy strategic role in corporate success, security and sense of belonging was more important in determining workers morale and productivity. That the study revealed that challenges faced by the employees in government entities as prevailing negative attitudes about government and government employees, frequent and abrupt changes in leadership, different employee motivations, strong civil-service rules and employee protections, constraints on the use of financial incentives. The study findings concluded showing the impact of employee relations used at Kabale district local government as regulations and agreements by which employees are managed both as individuals and the organization, promotes teamwork which achieves organization goals, employees will be treated fairly and honestly. Finally the study recommended that employees' input should be recognized and valued by the employer.